2008
DOI: 10.1363/3412708
|View full text |Cite
|
Sign up to set email alerts
|

Husband-Wife Agreement, Power Relations and Contraceptive Use in Turkey

Abstract: There are very few couple-level studies of communication and decision making regarding contraceptive use in the Middle East. In Turkey-a predominantly Muslim nation that has a secular democracy and is undergoing considerable social change-fertility has declined significantly, men play a major role in contraceptive practice and women's position in society is increasingly contested. These factors make Turkey a particularly interesting country for couplelevel studies.Traditionally, the measurement of contraceptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 22 publications
1
33
0
1
Order By: Relevance
“…This may again partly explain women's lack of decision making power over their contraceptive choice or their partners' influence. In fact, there are many evidences including a study in Turkey and Bangladesh that indicated spousal attitude and approval influence contraceptive use [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…This may again partly explain women's lack of decision making power over their contraceptive choice or their partners' influence. In fact, there are many evidences including a study in Turkey and Bangladesh that indicated spousal attitude and approval influence contraceptive use [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Such power relations tend to be less important in non-marriage situations such as those involving career-minded young women who are unmarried and have consensual relations with men. The analysis of the influences of power relationships, within marriage and informal unions, on the use of contraceptives by women show mixed results [32].…”
Section: Awareness and Use Of Birth Control Methodsmentioning
confidence: 99%
“…Several studies have examined how wife's and husband's fertility intentions predict future fertility and contraceptive use and results indicate that incorporating both spouses' attitudes improves predictability compared to including just one spouse's attitudes [1][2][3][4][5] . Results vary regarding which spouse's fertility intentions has greater predictive value.…”
Section: Introductionmentioning
confidence: 99%